Antibacterial effects of Lactococcus lactis isolated from Lighvan cheese regarding the recognition of Nisin, Lacticin and Lactococcin structural genes. (March 2018) - Attar, Mohammad Ali; Yavarmanesh, Masoud; Mortazavi, Ali; Edalatian Dovom, Mohammad Reza; Habibi Najafi, Mohammad Bagher
Abstract: The aim of this study was to evaluate the antibacterial effects of Lactococcus lactis isolated from Lighvan cheese with a focus on the recognition of Nisin, Lacticin and Lactococcin structural genes. For this purpose 1500 similar colonies from fresh grass, fresh milk, Curds, fresh cheese and ripe cheese were isolated based on morphology from 2 traditional factories in Lighvan region. After microscopic observations, 625 isolates were chosen and special biochemical experiments were carried out during which 60 suspicious isolates of Lactococcus lactis were recognized. To specify the exact species and subspecies, isolates were recognized by sequencing of 16SrRNA gene region and determined as Lactococcus lactis ssp. lactis. Antimicrobial evaluation was carried out using Agar spot and Well Diffusion techniques. Twelve isolates were positive according to antimicrobial properties and molecular experiments using specific primers. Our results showed that the frequency of antibacterial structural genes Lactococcin M, Lactococcin B, Lactococcin GQ, Lactococcin A and Nisin were 7, 6, 6, 1 and 1 out of 12 isolates, respectively. Highlights: Identification of Lactococcus lactis from different stages of Lighvan cheese. Detection of bacteria with inhibitory properties against some pathogenic bacteria. Detection of structural genes encoding nisin, lacticin and lactococcin.